DEVELOPMENT OF CONTROL AND MONITORING SYSTEM FOR ILLUMINATION OF THE DEPARTMENT OF ELECTRICAL ENGINEERING BASED ON THE INTERNET OF THINGS (IOT) - Muliadi Muliadi; Ruslan Ruslan; Riska Iqbal (Jurnal Media Elektrik, 2023)
This research is a research and development (R&D) study utilizing the prototype development model. The aim of this study is to produce a development of an internet of things-based lighting control system. The functionality testing results achieved a 100% score, indicating that the prototype is suitable for use, and the user response results obtained a 100% score with the "Very Good" category. The testing results for the response time of the lamp for on/off commands showed a duration of 0-6 seconds, and the speed of feedback notifications from Telegram was 0-6 seconds. The testing for the speed of checking the lamp status ranged between 0-6 seconds. Meanwhile, for the LDR sensor trial, it successfully achieved 100% in sending notifications about the lamp's condition when a status check command is given.